Atrial fibrillation in cancer patients: Hindsight, insight and foresight. (1st August 2017) - Mery, Benoîte; Guichard, Jean-Baptiste; Guy, Jean-Baptiste; Vallard, Alexis; Barthelemy, Jean-Claude; Da Costa, Antoine; Magné, Nicolas; Bertoletti, Laurent
Abstract: An increase of atrial fibrillation (AF) incidence in cancer patients has recently been pointed out, with complex interrelationships between these two entities on top of surgery factors. Most of present knowledge comes from retrospective studies or data from registries but the underlying mechanisms of the association between atrial fibrillation and cancer are still unclear. An increased risk of AF in cancer patients could represent a major public health problem although scarce information is available for the challenging management of such patients with distinctive features, especially in terms of antithrombotic therapy. Elaborate evidence-based approaches are thus required. This review provides an insight into AF among cancer patients through an overview of the underlying mechanisms, epidemiology evidence and future therapeutic challenges.